DAYA HAMBAT DAUN ALPUKAT MUDA TERHADAP BAKTERI MULUT (STREPTOCOCCUS MUTANS) - Prasko Prasko; Bambang Sutomo; Suwarsono Suwarsono; Iman Supardan (Jurnal Kesehatan Gigi, 2015)
TITLEInhibitory effect of young-avocado leaf against oral bacteria (Streptococcus mutans)ABSTRACTDental caries is one of the oral health problems that can cause pain and disrupt the activities. Bacteria plays an important role in the process of dental caries. The main bacterial cause of dental caries is Streptococcus mutans producing the glucosyltransferase enzyme. Streptococcus mutans produces a sticky extracellular polysaccharides of carbohydrate foods and able to ferment carbohydrates to acids. Streptococcus viridans is bacteria in the mucosa that synthesize large polysaccharides like dextran and levans of sucrose that are important factor in the formation of dental caries.This study aimed to determine the effectiveness of avocado leaf extract concentration of 60% and 80% to the inhibition of the growth of Streptococcus mutans.Method used was the method of diffusion wells using 2 samples in each treatment group. Sample consisted of 3 treatment groups  avocado young leaf extract concentration of 60%, 80%. This research data analysis method using quantitative descriptive.The results showed that the leaf extract of avocado at all concentrations have antibacterial activity against Streptococcus mutans. The lowest concentration of 60%,80% inhibition against the bacteria have a strong and increasingly stronger at higher concentrations. The conclusion of this study prove that avocado leaf extract has strong antibacterial activity against the growth of Streptococcus mutans. Key words : Avocado Young Leaf, Streptococcus Mutans